Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/modpathol.3800644
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CD117 expression in hypopigmented mycosis fungoides correlates with hypomelanosis: lessons learned from vitiligo

Abstract: Hypopigmented mycosis fungoides is an uncommon clinical variant of cutaneous T-cell lymphoma. We hypothesized that hypomelanosis in hypopigmented mycosis fungoides may have a similar mechanism as in vitiligo, a condition in which it is believed that alterations in expression of CD117 (stem cell factor receptor/KIT protein) on epidermal melanocytes and abnormal interactions between melanocytes and surrounding keratinocytes may play a pathogenic role. To test the hypothesis that similar mechanisms might also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 28 publications
4
44
0
1
Order By: Relevance
“…Unlike conventional MF, a disease typical of the fifth to sixth decades of life, HMF affects a younger population, even children [2,4,7,8,9,10]. Our data confirm the relatively young age at onset.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Unlike conventional MF, a disease typical of the fifth to sixth decades of life, HMF affects a younger population, even children [2,4,7,8,9,10]. Our data confirm the relatively young age at onset.…”
Section: Discussionsupporting
confidence: 76%
“…In HMF, however, several studies have shown a predominant CD8+ cell epidermotropism [4,5,9,11]. On the other hand, some papers have confirmed a predominance of CD4+ T cells [8].…”
Section: Discussionmentioning
confidence: 99%
“…Histologic studies have observed a decrease or absence of melanocytes within the lesions of vitiligo, 3,9 a finding that has also been seen, to a lesser extent, in hypopigmented MF. 6,10 Aside from this finding, vitiligo usually shows unremarkable changes with routine histologic staining.…”
Section: Discussionmentioning
confidence: 90%
“…This uncommon hypopigmented variant of MF has been more often observed in dark-complexioned individuals and predominantly in children, 1,2 comprising 17% of juvenile-onset cases. 3 The diagnosis of hypopigmented MF in children can be a challenging one to make. It initially may not be clinically suspected and therefore may be underdiagnosed or misdiagnosed as a more common condition, such as atopic dermatitis, postinflammatory hypopigmentation, or vitiligo.…”
mentioning
confidence: 99%
“…within the epidermis [17]. So, the aim of this study was to assess the immunohistochemical expression of CD117 in some pigmentary disorders such as melasma and vitiligo.…”
Section: Introductionmentioning
confidence: 99%